(untitled) (Research, Society and Development, 2021)
Use of mesenchymal stem cells and low-level laser therapy (LLLT) have been widely studied to promote bone healing. evaluate effect of photobiomodulation on total number of cells (TNC) and cell viability (CV) of fresh bone marrow aspirate (BMA). Femur BMA from 10 adult rats was collected and a cell concentration of 1x107 cell/mL was obtained. Cell suspension was deposited on 96 well cell culture plates and distributed in groups: 1) RPMI, positive control; 2) Distilled Water, negative control; 3) Red Laser (RL); 4) Infrared Laser (IRL). Groups RL and IRL received LLLT application right after incubation. Cells were incubated for 24 h. TNC and CV were assessed through trypan blue assay after 1, 3, 6, 10 and 24 h of incubation. Data distribution was verified by Shapiro-Wilk test. Kruskal-Wallis test was used for intergroup and intragroup comparisons (p<0.05). TNC: after 1 and 3 h, groups RL and IRL presented significantly higher TNC than Group Water; after 6 and 10 h, groups RPMI, RL and IRL presented significantly higher TNC than Group Water. CV: after 1 h, groups RL and IRL showed significantly higher percentage of VC than Group Water; after 3, 6 and 10 h, all groups presented significantly higher percentage of VC than Group Water. It can be concluded that LLLT enhanced number and viability of fresh bone marrow aspirate cells.